REVISING THE 'TENTATIVE STATEMENT' - Mautz, R. K. (The Accounting Review, 1941)
Since the Tentative Statement of Accounting Principles was published in 1936, a considerable critical and explanatory literature has developed on the general subject. No doubt the time will come when this discussion will inspire a reexamination and perhaps a revision of the original statement. With this in mind, the article reviews the Tentative Statement. Several general conclusions may be drawn from an examination of the published criticisms of the Tentative Statement. First, several of the propositions are considered by the critics as being applications of principles rather than principles in themselves. Second, the critics seem to offer no objection to the inclusion of what are essentially definitions and rules. Third, the implication is made that the Statement would have been better constructed, not as a series of equally important propositions, but as principles and corollaries. Fourth, some of the propositions, although challenged, are left in rather an uncertain state because the critics disagree as to whether there is sufficient reason to reject them. Fifth, the wording in many cases has been described as vague, ambiguous, and inconsistent proposals are made for new and additional principles not included in the Tentative Statement.